Studying the Moulding Ways for the Metal Powdered Aluminum Reinforced with Carbon Fiber in the Spark Plasma Sintering Process; Key Engineering Materials; Vol. 769 : High Technology: Research and Applications (HTRA 2017) - Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Shanenkova Yu. L. Yuliya Leonidovna; Polovinkina Yu. N. Yuliya Nikolaevna (2018, 2018)
Title screen